If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 12 + x = 47 Reorder the terms: 12 + 6x + x = 47 Combine like terms: 6x + x = 7x 12 + 7x = 47 Solving 12 + 7x = 47 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 7x = 47 + -12 Combine like terms: 12 + -12 = 0 0 + 7x = 47 + -12 7x = 47 + -12 Combine like terms: 47 + -12 = 35 7x = 35 Divide each side by '7'. x = 5 Simplifying x = 5
| 5x+20+3x+16=180 | | r-85=8 | | 5+8(1-7x)=-43 | | -5k+2=0 | | logx=.7 | | -2a+5(1-5a)=113 | | 110+0.80x=50+0.90x | | 7n-30=5 | | 6(5a+1)=-84 | | 5-(-7a)=-33 | | 3x+38=8x-12 | | hj=328 | | 3r-8=-32x | | T=2lw+2lh+2wh | | 4n-4=6 | | -14x+18+2x=54 | | 2r-3.1=7 | | 192=-2x+8(5-7x) | | logx=1.22 | | n*-7-2=10 | | 3x-3(-5x+4)=-120 | | 2x+13=5y | | 11x-12-2x=15 | | 11mn-2mn+9= | | 0.23x=1.48 | | 259=7(8x+5) | | x^3+12x-24=0 | | 7r+6r=-13 | | 14x+1=-2+8x+15 | | -14=b-2-8 | | 7x+23-2x=53 | | 1+2x-3x=9 |